Acetylcholinesterase (AChE) and heat shock proteins (Hsp70) of gypsy moth (Lymantria dispar L.) larvae in response to long-term fluoranthene exposure. (September 2016) - Mrdaković, Marija; Ilijin, Larisa; Vlahović, Milena; Matić, Dragana; Gavrilović, Anja; Mrkonja, Aleksandra; Perić-Mataruga, Vesna
Abstract: Polycyclic aromatic hydrocarbons (PAHs) may affect biochemical and physiological processes in living organisms, thus impairing fitness related traits and influencing their populations. This imposes the need for providing early-warning signals of pollution. Our study aimed to examine changes in the activity of acetylcholinesterase (AChE) and the concentration of heat shock proteins (Hsp70) in homogenates of brain tissues of fifth instar gypsy moth ( Lymantria dispar L.) larvae, exposed to the ubiquitous PAH, fluoranthene, supplemented to the rearing diet. Significantly increased activity of AChE in larvae fed on the diets with high fluoranthene concentrations suggests the necessity for elucidation of the role of AChE in these insects when exposed to PAH pollution. Significant induction of Hsp70 in gypsy moth larvae reared on the diets containing low fluoranthene concentrations, indicate that changes in the level of Hsp70 might be useful as an indicator of pollution in this widespread forest species. Highlights: Long-term effects of PAH fluoranthene were examined in the fifth instar gypsy moth. Increased AChE activity was recorded in brain tissues at higher PAH concentrations. Elevated Hsp 70 levels were detected in brain tissues at lower PAH concentrations. Detected changes were suggested as useful indicator of PAH pollution.